2018
DOI: 10.1590/1983-21252018v31n214rc
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fertilization for Optimization of Onion Production

Abstract: Information about the response of onion to different potassium doses may contribute to optimizing the use of fertilizers and, consequently, make the activity more profitable and environmentally sustainable. In this context, the aim of this study was to evaluate the effects of doses of potassium on onion yields. Two field experiments were carried out in the periods of September to December 2012 and April to July 2013. The experimental design used was completely randomized blocks with four replications. The trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 5 publications
1
7
2
Order By: Relevance
“…The higher concentrations of nitrogen during vegetative period can be attributed to the active growth at this stage, resulting in partitioning of the nutrients to the above-ground plants. Increasing the dosage of potassium from 36 to 180 kg K 2 O per ha significantly increased onion yield, with bulb production at 180 kg K 2 O per ha being 22.8% higher than without fertilizer, while the leaf potassium contents of onion with no fertilizers was still within the sufficiency range (Marrocos et al, 2018). In our study, we did not notice the symptoms of N, P or K deficiency in the control plants.…”
Section: Bulb Production In E Bulbosacontrasting
confidence: 57%
“…The higher concentrations of nitrogen during vegetative period can be attributed to the active growth at this stage, resulting in partitioning of the nutrients to the above-ground plants. Increasing the dosage of potassium from 36 to 180 kg K 2 O per ha significantly increased onion yield, with bulb production at 180 kg K 2 O per ha being 22.8% higher than without fertilizer, while the leaf potassium contents of onion with no fertilizers was still within the sufficiency range (Marrocos et al, 2018). In our study, we did not notice the symptoms of N, P or K deficiency in the control plants.…”
Section: Bulb Production In E Bulbosacontrasting
confidence: 57%
“…However, no symptoms of K deficiency were observed, even in the treatment without the addition of this nutrient. A positive response to K fertilisation, but with leaf contents of this nutrient superior to those obtained in this experiment, was verified by Marrocos et al (2018), who evaluated the effect of cultivation periods and K doses on the cultivar 'IPA 11', obtaining average leaf K contents of 51.22 and 43.84 g kg -1 in September/2012 and April/2013, respectively.…”
Section: Resultssupporting
confidence: 72%
“…An explanation for this difference may be related to the interaction in the soil between K and the elements Ca and Mg since in the soil (Argissolo Vermelho Amarelo -Ultisol) used by Marrocos et al (2018), this ratio was 6.4, whereas, in the present study, it was 14.0. The effect of the (Ca+Mg)/K ratio on the absorption of these three elements in the vegetative part of the garlic crop was observed by Bull et al (1998), who found that that the reduction in this ratio from 207.3 to 1.9 practically quadrupled the leaf K content.…”
Section: Resultscontrasting
confidence: 61%
See 1 more Smart Citation
“…Potassium can improve plant strength and health because it plays an important role in plant physiology, including in the synthesis, transportation, and storage of assimilation products (BUKHSH et al, 2012;HAWKESFORD et al, 2012). Potassium is an important nutrient for shallots in agricultural culture, and several studies have shown that the accumulation of potassium varies according to cultivar and planting location (VIDIGAL; MOREIRA; PEREIRA, 2010; AGUIAR NETO et al, 2014;MARROCOS et al, 2018).…”
Section: Introductionmentioning
confidence: 99%